Opportunities for learning: the use of variation to analyse examples of a paradigm shift in teaching primary mathematics in England. Issue 1 (2nd January 2019) - Al-Murani, Thabit; Kilhamn, Cecilia; Morgan, Debbie; Watson, Anne
ABSTRACT: We demonstrate the power of Variation Theory as an analytical tool used to understand the underlying conceptual structure of mathematics lessons taught by English primary school teachers. We study excerpts of three lessons that are posted on a professional website. We show how lesson analysis using variation allows us to focus on what is made available to be learnt in the lesson excerpts. We identify some differences in their use of dimensions of variation and the associated ranges of change and discuss how suitable patterns of variation and invariance might differ according to the nature of the learning focus. We reflect on the value of our analytical approach.